Ultrasonic and vacuum system integrated additive manufacturing: a new approach to reduce staircase effect of 3d printed parts - Mohamed, Ahmad Syafiq; Maidin, Shajahan; Abdul Hamid, Rahimah (Penerbit UTeM Press, 2023)
This book introduces basic concepts and methodologies for mobile robot design, development, and evaluation. developed for the course Advanced Robotics and Robotics Laboratory taught by the author at Universiti Teknikal Malaysia Melaka. The book provides the foundation for further study in the field of mobile robots.